(untitled) (Iraqi Journal of Medical Sciences, 2017)
Background: Hypospadias describes a urethral opening proximal to the normal position at the glandular tip (anywhere on the ventral surface) and it is considered the most common penile anomaly. There are many surgical modalities for reconstruction but with different success. The goal of modern hypospadias repair is to achieve functionally as well as cosmetically normal looking glans, meatus and phallus. Snodgrass urethroplasty was introduced in 1974 with more reliable creation of a normal appearing meatus. Objective: To see the short-term results of tubularized incised plate urethroplasty as described by Snodgrass in mid and distal penile hypospadias. Methods: This is a prospective study for evaluation of fifty male children with age ranged from one to ten years with penile hypospadias (distal and mid shaft) were included in this study over a period from January 2008 to January 2016 in our pediatric surgical center. Results: The majority were between 2-4 years. Meatal stenosis (12%) and urethrocutaneous fistula (6%) were the most common complications encountered in this study. Inguinal hernia (8%) and undescended testis (10%) were the most common associated congenital anomalies with hypospadias. Conclusion: Snodgrass urethroplasty is simple, single stage operation in the management of mid and distal penile hypospadias with good cosmetic and functional results. Keywords: Hypospadias, Snodgrass technique, meatal stenosis, urethrocutaneous fistula. Citation: Zain AZ. Snodgrass urethroplasty for mid and distal penile hypospadias. Iraqi JMS. 2017; Vol. 15(3): 283-287. doi: 10.22578/IJMS.15.3.10